Pembuatan Aplikasi Point of Sales dan Online Shop Berbasis Web Menggunakan Framework Laravel - Liem Kevin Christian Halim; Justinus Andjarwirawan (Jurnal Infra, 2017)
Trade is an activity of the transaction between seller and buyer. These transactions are usually in the form of exchange of money the buyer with the goods or services from sellers. For many people trading is also an opportunity to increase their profits. But they must be good at predicting consumer demand, to minimize expired goods that would result in losses and thus reduce profit for the company or shop.One of the quick solution to reduce the problems is to use software to predict the future of the cash flow in the store. So that can reduce the amount of loss of cash in the store because of run out of stocks or expired items.Point Of Sales is a software system that can record every transaction made by the seller and the buyer. This system can record every detail accurately.